Causal mechanisms of a healthy lifestyle intervention for patients with musculoskeletal pain who are overweight or obese. (June 2019) - Williams, Amanda; Lee, Hopin; Kamper, Steven J; O'Brien, Kate M; Wiggers, John; Wolfenden, Luke; Yoong, Sze L; Hodder, Rebecca K; Robson, Emma K; Haskins, Robin; McAuley, James H; Williams, Christopher M
Purpose: To assess the causal mechanisms of a healthy lifestyle intervention for patients with chronic low back pain and knee osteoarthritis, who are overweight or obese. Methods: We conducted causal mediation analyses of aggregated data from two randomized controlled trials (RCTs); which included 160 patients with chronic low back pain, and 120 patients with knee osteoarthritis. The intervention consisted of brief advice and referral to a six-month telephone-based healthy lifestyle coaching service. We used causal mediation to estimate the indirect, direct and path-specific effects of hypothesized mediators including: self-reported weight, diet, physical activity, and pain beliefs. Outcomes were pain intensity, disability, and quality of life (QoL). Results: The intervention did not reduce weight, improve diet or physical activity or change pain beliefs, and these mediators were not associated with the outcomes. Sensitivity analyses showed that our estimates were robust to the possible effects of unknown and unmeasured confounding. Conclusions: Our findings show that the intervention did not cause a meaningful change in the hypothesized mediators, and these mediators were not associated with patient-reported outcomes.